How professors think inside the curious world of academic judgment - Lamont, Michèle 1957- (Harvard Univ. Press, 2009)
Judging quality isn't robotically rational; it's emotional, cognitive, and social, too. Yet most academics' self-respect is rooted in their ability to analyze complexity and recognize quality, in order to come to the fairest decisions about that elusive god, "excellence." In How Professors Think, Lamont aims to illuminate the confidential process of evaluation and to push the gatekeepers to both better understand and perform their role. --from publisher description
Literaturverz. S. 289 - 315
Keywords: Enseignants - Efficacité; Evaluatie; Kwaliteit; Meningsvorming; Peer review; Portfolios en éducation; Professeurs (Enseignement supérieur) - Évaluation; Vakgebieden; Wetenschap; Wetenschapsbeoefening; Wissenschaft; Évaluation par des pairs; College teachers -- Rating of; Teacher effectiveness; Portfolios in education; Qualitätssicherung; Evaluation; Bewertung; Hochschullehrer; Peer-Group; Forschung; USA